Attitudinal and behavioural responses to increasing tobacco control regulation among high smoking prevalence groups: A qualitative study - Parnell, A.; Box, E.; Biagioni, Nicole; Bonevski, B.; Coffin, J.; Slevin, Terry; Anwar-McHenry, J.; Pettigrew, Simone (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Australasian Professional Society on Alcohol and other Drugs Introduction and Aims: Despite substantial reductions in smoking prevalence in many countries, rates remain high among people who are experiencing disadvantage. This study aimed to explore attitudinal and behavioural responses to population-wide tobacco control policies among Australian smokers experiencing disadvantage. Design and Methods: Semi-structured qualitative interviews were conducted with 84 smokers attending community service organisations in the mental health, homelessness, and alcohol and other drug sectors. Interviewees discussed various tobacco control policies (tobacco taxes, smoke-free areas, plain packaging and graphic health warnings). The interview transcriptions were coded and thematically analysed. Results: Responses to tobacco taxes were mixed. Some interviewees reported smoking less as a result of price increases, while others reallocated funds from other budget areas. Many perceived smoke-free area policies as effective, although some described strategies they use to circumvent this policy, thereby diminishing its effectiveness. Plain packaging and graphic warnings were perceived as being least effective. Discussion and Conclusions: While tobacco control policies can elicit intended attitudinal and behavioural responses, additional efforts are needed to enhance their effectiveness among smokers experiencing disadvantage. Future efforts to reduce smoking rates should address responses that diminish policy effectiveness among groups exhibiting high smoking prevalence. This could be achieved through strategies that address the specific needs of these groups, such as providing additional cessation support, enforcing existing smoke-free policies in ways that minimise inequitable effects, and addressing self-exempting beliefs.